Space data system protocols and application software for Leo satellite systems - Lim, Sharon Siok Lin. (2008)
This thesis addresses the design and implementation of an onboard Telemetry and Telecommand module for LEO spacecraft. An internationally accepted Space Communication Standard developed by the Consultative Committee for Space Data System (CCSDS) has been adopted for this satellite module. The 7 layer functionality of the CCSDS recommendations for Telemetry and Telecommand is discussed. In particular, the implementation aspects of its top three layers, which pertain to the CCSDS Data Management Service functions, are dealt with in detail. A particular implementation of an onboard network, based on the Controller Area Network Protocol Specifications, have been developed to support the higher layer Telemetry and Telecommand functionality of the CCSDS protocol.